Analysis of Multicultural Islamic Religious Education Learning: Case Study at State Elementary School (SDN) of 01 Sidoarjo, Way Kanan Regency - Amad Sutami; Subandi Subandi; Siti Roudhotul Jannah (Journal of Research in Islamic Education, 2022)
The purpose of this study includes how the application and its effect on learning through the application of strategies and concepts of learning Islamic religious education based on the utilization of ethnic, cultural and religious diversity that exists in society. The methods used to collect data in this study were observation, interviews and documentation through a case study approach, deductive and inductive in analyzing the data that had been obtained and using qualitative descriptive analysis. The object of this research is class V.A students in the even semester of the 2020/2021 school year. The results of the study indicate that multicultural-based Islamic Religious Education learning has an influence on multicultural understanding for students at SDN. 01 Sidoarjo, Way Kanan Regency, this can be seen from 24 students who stated that they were happy, 20 (83.3%), who stated that they did not like 3 students (12.5%) and who stated that they were ignorant only 1 student (4.2%). It can be concluded that multicultural-based Islamic Religious Education learning has a high influence on multicultural understanding for students